Development and psychometric assessment of the sexual-reproductive health profile of women with type-1 diabetes mellitus - Nasrin Azimi; Giti Ozgoli; Abbas Ebadi; Hamid Alavi Majd; Assadollah Rajab; Zahra Kiani; Shahin Bazzazian; Tahereh Mokhtaryan-Gilani (BMC, 2022)
Abstract Background To improve the sexual-reproductive health (SRH) of women with type-1 diabetes mellitus (T1DM), plans should be formulated on the basis of the existing situation. The situation can be examined by a valid tool conforming to the specific domains of SRH in the target group. The present study seeks to develop and assess the psychometric properties of the SRH Profile of Women with T1DM. Method Based on the extracted concepts of SRH Profile of Women with T1DM in a previously conducted study, a tool was designed using the following steps: The selection of the conceptual model, explaining the objectives, designing the roadmap and development of the tool. In the psychometric assessment phase, the content, face and construct validity (convergent validity and principal component analysis) were assessed with the participation of 365 married women of reproductive age with T1DM. The reliability of the tool was determined by the internal consistency method (Cronbach's alpha) and its stability using the test-retest method (Intraclass Correlation Coefficients). Results The SRH Profile of Women with T1DM was formed with 53 items in two sections. Twenty-six items were about safe motherhood and reproductive system; 27 items were about the three components of concerns about the reproductive system health and function, sexual health and function, and violence related to T1DM. The three components in the second section explained 49.44% of the total variance. Cronbach's alpha was 0.872 and the total intra-cluster correlation coefficient was 0.946. Conclusion SRH Profile of Women with T1DM is a valid, reliable, and specific tool for assessing sexual-reproductive health in women with type-1 diabetes mellitus.